Shared decision making and advance care planning-underpinnings, similarities and differences. Issue 2 (1st June 2012) - Krones, T; Biller Andorno, N; in der Schmitten, J; Mitchell, C; Spirig, R; Zaugg, K
Abstract : There are two movements, each rooted in bioethics and evidence-based medicine, that focus on quite similar aims yet are not fully aligned and integrated in the clinical care of dying patients: The first, "advance care planning" focusses on future decisions when one becomes incapable of decision making, and the second, "shared decision making" has led to decision aids designed on the basis of empirical evidence to solicit and support patients' choices and decisions. The aim of our study, beginning in 2012, is to develop, implement and test a complex intervention (continuous multi-professional development – CPD program) for improving patients' preparation for and participation in end of life decisions including both strategies ACP and SDM/DA on end of life issues in an acute care hospital setting. In order to prepare for our randomised controlled trial, we systematically screened existing ACP and SDM programs for end of life issues and analysed their content, scope, aims, similarities and differences. The SDM philosophy relies more on giving tailored statistical information on distinct measures whereas ACP relies more on defining broader goals of care, which might indicate not only different contents but also differing concepts of autonomy. Outcomes are both similar and different. For example, both investigate impact on satisfaction with care and economy. SDM focuses more on knowledge and decisional conflict whereas ACP focuses on numbers of advance directives (ADs), and decisions made according to wishes. We will discuss philosophical and practical underpinnings of bringing the two movements together.